The Role of Parents in Forming Children's Financial Literacy from an Early Age - sidiq, fahmi; Ibrahim, Riza Andrian; Pirdaus, Dede Irman (Research Collaboration Community (RCC), 2024)
This research illustrates the importance of introducing the concept of income and expenditure at an early age by presenting simple, relevant examples. The introduction of income, such as a weekly allowance from parents, helps children understand the meaning of effort in earning money, develops financial decision-making skills, and builds discipline. Positive impacts include a better understanding of financial concepts and growing financial independence, despite potential wasteful habits and dependence on parents. On the other hand, the introduction of expenses, such as buying snacks or toys, helps children learn to choose between different options, understand the value of money, and be responsible for their spending. It also strengthens financial decision-making skills and awareness of financial priorities, although it can lead to wasteful habits and lack of awareness about saving for the future. In conclusion, early financial literacy education has a key role in shaping children's understanding of finance, financial values, and wise financial management practices, which will help them face future financial challenges and build a more stable financial foundation, while creating a strong foundation for healthy financial understanding within the family.